1993
DOI: 10.1002/1097-0142(19931215)72:12<3599::aid-cncr2820721209>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Loxiglumide (CR1505), a cholecystokinin antagonist, specifically inhibits the growth of human pancreatic cancer lines xenografted into nude mice

Abstract: Background. Cholecystokinin is thought to be an important factor regulating the growth of human pancreatic cancers. The study was designed to evaluate the effects of the cholecystokinin antagonist loxiglumide (CR1505) on the growth of human pancreatic cancer. Methods. Human gastrointestinal cancer xenografted tumors (one esophageal, one gastric, two colorectal, two biliary tract, and two pancreatic cancers) were transplanted into nude mice. The mice were given CR1505 at 250 mg/kg daily for 14 days, either subc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…However, stimulative, inhibitory or no effect of CCK on the growth of human pancreatic cancer cell lines or human pancreatic cancer xenografts in nude mice have been reported (Upp et al, 1987;Smith et al, 1990;Nio et al, 1993). Although the membrane fractions of some pancreatic cancer cell lines, such as MIA PaCa-2, BxPC-3, Capan-1, MDA-Amp-7 and MDA-Panc-28, expressed CCK-B receptors (Smith et al, 1994), no specific CCK binding was detected in the membranes of other pancreatic cancer cell lines (Singh et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…However, stimulative, inhibitory or no effect of CCK on the growth of human pancreatic cancer cell lines or human pancreatic cancer xenografts in nude mice have been reported (Upp et al, 1987;Smith et al, 1990;Nio et al, 1993). Although the membrane fractions of some pancreatic cancer cell lines, such as MIA PaCa-2, BxPC-3, Capan-1, MDA-Amp-7 and MDA-Panc-28, expressed CCK-B receptors (Smith et al, 1994), no specific CCK binding was detected in the membranes of other pancreatic cancer cell lines (Singh et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, VSMCs showed decreased proliferation and motility in comparison to the control (Hemshekhar et al 2016 ; Li et al 2015a ; Li et al 2015b ; Yang et al 2015 ). TiO 2 NTs, as an example, introduced an effective drug-free approach for vascular healing (Hemshekhar et al 2016 ; Nio et al 1993 ; Yang et al 2012 ).Nuhn et al ( 2017 ) provided both in vitro and in vivo data on the implantation of TiO 2 -NT-covered stents (Hemshekhar et al 2016 ; Li et al 2017 ; Li et al 2015a ). The in vivo results were in agreement with the in vitro study which showed reduced restenosis rates, promoted restoration of a functional endothelium when compared to the control.…”
Section: Surface Coating Techniquesmentioning
confidence: 99%
“…CCK receptors actiwtted by CCK may stimulate the growth of human pancreatic c; ncer cell lines [13]. LXG, a specific CCK receptor antagonst, has been reported to inhibit DNA synthesis and the gowth of human pancreatic cancer [16]. Many previous rep)rts have provided evidence in support of CCK receptors paying as growth factor receptors.…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, a clinical trial has reported that LXG may be a useful agent for pmcreatitis [15]. A recent study has reported that LXG inh bits the growth of human pancreatic cancer cell lines [16]. tiowever, no known study has reported the relationship between CCK receptors and the invasiveness of human panc~eatic cancer cells.…”
Section: Introductionmentioning
confidence: 99%